2008
DOI: 10.1002/ccd.21549
|View full text |Cite
|
Sign up to set email alerts
|

Catheter‐based treatment of the subclavian and innominate arteries

Abstract: Catheter-based revascularization with stents for symptomatic S/IA lesions is safe and effective with excellent patency rates and sustained symptom resolution in the majority (>80%) of patients over 3 years of follow-up. Percutaneous primary stent therapy is the preferred method of revascularization in patients with suitable anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
54
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(64 citation statements)
references
References 25 publications
9
54
0
1
Order By: Relevance
“…22 The wide range of success (0-90.5%) reported in the literature might be due to the high variation in experience of interventionalists with regard to complete occlusions. 22,23 This is emphasized by the very high success rate of 86% in the present study and 90% in the Patel et al study, both of which represent the largest available studies at centers with considerable experience in that field. 23 Given that no randomized trials are available to date, there is currently insufficient evidence to determine whether stentsupported angioplasty is favorable over plain angioplasty without stenting.…”
supporting
confidence: 47%
See 1 more Smart Citation
“…22 The wide range of success (0-90.5%) reported in the literature might be due to the high variation in experience of interventionalists with regard to complete occlusions. 22,23 This is emphasized by the very high success rate of 86% in the present study and 90% in the Patel et al study, both of which represent the largest available studies at centers with considerable experience in that field. 23 Given that no randomized trials are available to date, there is currently insufficient evidence to determine whether stentsupported angioplasty is favorable over plain angioplasty without stenting.…”
supporting
confidence: 47%
“…22,23 This is emphasized by the very high success rate of 86% in the present study and 90% in the Patel et al study, both of which represent the largest available studies at centers with considerable experience in that field. 23 Given that no randomized trials are available to date, there is currently insufficient evidence to determine whether stentsupported angioplasty is favorable over plain angioplasty without stenting. 24 While some studies showed at least a trend towards an advantage of stenting over plain angioplasty, 25 others reported no significant difference between the treatment strategies.…”
supporting
confidence: 47%
“…In a study by Patel et al, 14 indications for revascularization included arm ischemia (57%), vertebral-subclavian steal syndrome (37%), coronary-subclavian steal syndrome (21%), and planned coronary bypass surgery using the ipsilateral internal mammary artery (8%).…”
Section: Treatmentmentioning
confidence: 99%
“…Of 107 cases (108 lesions) reported by Sixt et al 9 , the technical success rate was 96% (100% for stenosis (78/78) and 87% for total occlusions (26/30)), treatment modalities included PTA alone (13%) or stenting (87%), and the mortality rate and morbidity rate were both 0%. Patel et al 10 , in a study of 170 cases (177 lesions), reported a technical success rate of 98.3% (99.4% for stenosis (155/156) and 90.5% for occlusions (26/30)), all underwent primary stent placement, and stroke in one patient (0.6%, not described about distal protection of vertebral artery). Thus, technical success rates were high, and perioperative complication rates were low.…”
Section: Discussionmentioning
confidence: 99%
“…Patel et al 10 , of 151 cases fol- lowed up, reported that during a mean observation period of 35.2 months, 14.6% required retreatment. Sixt et al, of 97 cases followed up, reported that during a mean observation period of 29 months 12% required retreatment.…”
Section: Discussionmentioning
confidence: 99%